PENILAIAN MUTU JAJANAN PASAR TRADISIONAL DI HOTEL LORIN SENTUL BOGOR - Tatik Sriwulandari; Ravi Darunadwah Ashidiqi (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
ABSTRACT This study aims to analyze the quality of traditional market snacks at the Lorin Sentul Hotel Bogor and to determine guest interest in the product. The main problems found were the remaining market snacks after being served and complaints related to taste and texture. The method used was descriptive quantitative with data collection through questionnaires to 35 hotel guests. The evaluation included nine dimensions of quality, namely color, appearance, portion, shape, temperature, texture, aroma, level of maturity and taste. The results showed that guest assessments of market snacks provided by the Lorin Sentul Bogor Hotel obtained an average score of 3.07 based on the assessment of nine dimensions, which means that guests gave a positive rating because this number shows the assessment scale in the category of liking. The maturity level dimension received the highest score with an average of 3.17 while the color combination received the lowest score with an average of 2.99. Quality improvement can be focused on dimensions with values below the average, namely color with a value of 2.99, aroma and portion with values of 3.01 each. The recommendations given are supervision of the market snack production process and training for pastry department employees so that presentation can be more optimal.